Memahami dan Menerapkan Prinsip Kepemimpinan Orang Muda Menurut 1 Timotius 4:12 bagi Mahasiswa Teologi - Samarenna, Desti; Siahaan, Harls Evan R. (Sekolah Tinggi Agama Kristen Negeri Toraja, 2019)
Leadership is mostly required in church management. There are many leadership characteristics in the Bible that can be used as leadership patterns in the church. This article is a literature study with a qualitative approach to the text of 1 Timothy 4:12 concerning the leadership of a young person, which aims to encourage students to understand and apply the pattern of leadership referred to in the text of 1 Timothy 4:12. The method used is descriptive analysis in the text of 1 Timothy 4:12, to provide a clear picture and understanding of the principles of the leadership of young people. In addition, descriptive methods are also used to determine students' understanding of the principles of leadership according to the text, as well as the level of application in life and service. In conclusion, students understand the principle of leadership in 1 Timothy 4:12, which is about giving an example, but not all students are ready and able to do it.AbstrakKepemimpinan merupakan hal yang sangat dibutuhkan dalam manajemen gereja. Ada banyak karakteristik kepemimpinan dalam Alkitab yang dapat dijadikan pola kepemimpinan dalam gereja. Artikel ini merupakan kajian literatur dengan pendekatan kualitatif terhadap teks 1 Timotius 4:12 tentang kepemimpinan seorang muda, yang bertujuan untuk mendorong mahasiswa memahami dan menerapkan pola kepemimpianan yang disebut dalam teks 1 Timotius 4:12 tersebut. Metode yang digunakan adalah deskriptif analasis pada teks 1 Timotius 4:12, untuk memberikan gambaran dan pemahaman yang jelas tentang prinsip kepemimpinan orang muda. Selain itu, metode deskriptif juga digunakan untuk mengetahui pemahaman mahasiswa tentang prinsip kepemimpinan menurut teks tersebut, serta tingkat penerapannya dalam kehidupan dan pelayanannya. Kesimpulannya, mahasiswa memahami prinsip kepemimpinan dalam 1 Timotius 4:12, yaitu tentang memberikan teladan, namun tidak semua mahasiswa siap dan mampu melakukannya.